2010
DOI: 10.1590/s0102-86502010000300013
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management in intrauterine surgery to evaluate an experimental model of myelomeningocele in non human primates (Macaca mulatta)

Abstract: Anesthetic management in intrauterine surgery to evaluate an experimental model of myelomeningocele in non human primates (Macaca mulatta) RESUMO Objetivo:Avaliar o manejo anestésico em cirurgia intra-uterina para induzir mielomeningocelo em primatas não humanos, Macaca mulatta. Métodos: Operaram-se um total de nove fetos in útero que foram submetidos à laminectomia em L5 e L6. As variáveis a estudar foram mortes maternas ou fetais, freqüência cardíaca e respiratória, pressão arterial, temperatura e saturação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Increases in CK have also been associated with a decrease in body temperature . This relates to descriptions in various articles which mention that the anesthetic combinations of ketamine‐xylazine and tiletamine‐zolazepam lower body temperature, and while the values we obtained are similar to those reported for CK and LDH, these statistical differences could be related to the anesthetic mixtures utilized . Finally, our study observed changes in electrolytes, including a decrease in Ca in the cases of KA and KX.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Increases in CK have also been associated with a decrease in body temperature . This relates to descriptions in various articles which mention that the anesthetic combinations of ketamine‐xylazine and tiletamine‐zolazepam lower body temperature, and while the values we obtained are similar to those reported for CK and LDH, these statistical differences could be related to the anesthetic mixtures utilized . Finally, our study observed changes in electrolytes, including a decrease in Ca in the cases of KA and KX.…”
Section: Discussionsupporting
confidence: 89%
“…Our results show that statistically significant differences in this regard occurred only in Group 3 when KX was compared to the control group. It is clear that while no significant differences appeared among the other groups for KA and KX, temperature always remained below the values obtained for the control group, though without exceeding the normal range (36‐40°C) …”
Section: Discussionmentioning
confidence: 58%
“…All monkeys were assessed as clinically healthy before the study began and showed no neurological or behavioral dysfunctions, except for the senile monkeys that by virtue of their age displayed a minor decrease in motion during ambulation, although otherwise appear healthy. SEPs of median and tibial nerves were performed in all monkeys under slight sedation using tiletamine + zolazepam (Zoletil ® , Virbac Laboratories, Carros, France) at a dose of 4 mg/kg body weight injected intramuscularly [2, 9].…”
Section: Methodsmentioning
confidence: 99%
“…Non‐human primates (NHP) have been an excellent biomodel for a large number of studies, being the rhesus monkey ( Macaca mulatta ) one of the most used species . Female rhesus macaques are non‐human primates with the reproductive tract anatomy and their 28‐day menstrual cycles similar to those of women ; human reproduction studies have reported that NHP are an excellent model for physiological and ontogenetic processes due to its position on the evolutionary tree, being the species phylogenetically more similar to humans . Regarding the good practice in laboratory work, it is essential to have sufficient information to enable a correct interpretation of all the results of this species, for handling and clinical supervision and specific protocols within many researches .…”
Section: Introductionmentioning
confidence: 99%